Pulmonary Vasculature Responsiveness to Phosphodiesterase-5A Inhibition in Heart Failure With Reduced Ejection Fraction: Possible Role of Plasma Potassium - Monzo, Luca; Reichenbach, Adrian; Al-Hiti, Hikmet; Jurcova, Ivana; Huskova, Zuzana; Kautzner, Josef; Melenovsky, Vojtech (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Phosphodiesterase-5a inhibition (PDE5i) leads to favourable changes in pulmonary hemodynamic and cardiac output (CO) in patients with advanced heart failure and reduced ejection fraction (HFrEF). The hemodynamic response to PDE5i could be heterogenous and the clinical variables associated to these changes are scarcely investigated. Material and Methods: From 260 patients with advanced HFrEF referred for advanced therapies (cardiac transplant/LVAD), 55 had pulmonary hypertension (PH) and fulfilled criteria for PDE5i vasoreactivity test. Right heart catheterization was performed as part of clinical evaluation before and after 20-mg intravenous sildenafil. Absolute and relative changes in pulmonary vascular resistance (PVR) were evaluated to assess hemodynamic response to PDE5i. Clinical, biochemical, and hemodynamic factors associated with PVR changes were identified. Results: Sildenafil administration reduced PVR (-45.3%) and transpulmonary gradient (TPG; - 34.8%) and increased CO (+13.6%). Relative change analysis showed a negative moderate association between baseline plasma potassium and changes in PVR (r= -0.48; p=0.001) and TPG (r= -0.43; p=0.005) after PDE5i. Aldosterone concentration shows a direct moderate association with PVR changes after PDE5i. A significant moderate association was also demonstrated between CO improvement and the severity of mitral (r=0.42; p=0.002) and tricuspid (r=0.39; p=0.004) regurgitation. Conclusions: We identified plasma potassium, plasma aldosterone level and atrioventricular valve regurgitations as potential cofounders of hemodynamic response to acute administration of PDE5i. Whether modulation of potassium levels could enhance pulmonary vasoreactivity in advanced HFrEF deserves further research.